Distal hereditary motor neuropathy in Korean patients with a small heat shock protein 27 mutation - Chung, Ki Wha (Korean Society of Medical Biochemistry and Molecular Biology, 2008)
Distal hereditary motor neuropathy (dHMN) is a heterogeneous disorder characterized by degeneration of motor nerves in the absence of sensory abnormalities. Recently, mutations in the small heat shock protein 27 (HSP27) gene were found to cause dHMN type II or Charcot-Marie-Tooth disease type 2F (CMT2F). The authors studied 151 Korean axonal CMT or dHMN families, and found a large Korean dHMN type II family with the Ser135Phe mutation in HSP27. This mutation was inherited in an autosomal dominant manner, and was well associated with familial members with the dHMN phenotype. This mutation site is located in the α-crystallin domain and is highly conserved between different species. The frequency of this HSP27 mutation in Koreans was 0.6%. Magnetic resonance imaging analysis revealed that fatty infiltrations tended to progressively extend distal to proximal muscles in lower extremities. In addition, fatty infiltrations in thigh muscles progressed to affect posterior and anterior compartments but to lesser extents in medial compartment, which differs from CMT1A patients presenting with severe involvements of posterior and medial compartments but less involvement of anterior compartment. The authors describe the clinical and neuroimaging findings of the first Korean dHMN patients with the HSP27 Ser135Phe mutation. To our knowledge, this is the first report of the neuroimaging findings of dHMN type II.